IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM- BASED LEARNING) DENGAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN HIGHER ORDER THINKING SKILLS PADA MAHASISWA PRODI PGSD FIP UNIMED - Lala Jelita Ananda; Fahrur Rozi; Akden Simanihuruk; Elvi Mailani (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2017)
This research conducted in PGSD FIP Unimed  to increase Higher Order Thinking Skills of PGSD students. Based on the research results, in the control class using the conventional method the average learning outcome 79.08 whereas with the model of Problem Based Learning learning with the scientific approach data average learning outcome is 83.03. Based on the calculation obtained Fhitung> Ftabel yaitu 6,53 > 2.67, then Ho is rejected and it can be concluded there are significant differences in implementation of Problem-based Learning model with scientific approach in increasing Higher Order Thinking Skills.Keywords: Higher Order Thinking Skilss, Problem-Based Learning, Scientific Approach